Effect of different sources of organic manures on growth and yield of Broccoli (Research in Agriculture Livestock and Fisheries, 2024)
Indiscriminate use of chemical fertilizers is a common practice that is hazardous both for soil health and the environment. It has been more than three decades that global agriculture has been depicted towards organic agriculture owing to sustainability and reduced environmental effects. An experiment was conducted in Randomized Complete Block Design (RCBD) with three replications to study the effect of different sources of organic nutrients on growth and yield of broccoli. The experiment consisted of five different sources of manures; control (no manure), cowdung (25 t/ha), Trichoderma compost (10 t/ha), vermicompost (12 t/ha) and poultry litter (14 t/ha) along with two cultivars of broccoli; ‘Imperial’ and ‘Premium Crop’. Different sources of manures and cultivars had significant influence on plant height, height up to curd, number of leaves per plant, length of leaf, breadth of leaf, plant canopy, diameter of curd, diameter of stem, weight of primary curd, number of secondary curds, weight of secondary curd, yield per plant, yield per unit plot and yield per hectare. The maximum yield (17.32 t/ha) was obtained from vermicompost, followed by poultry litter in ‘Premium Crop’ (15.68 t/ha) cultivar. The minimum yield (6.62 t/ha) was recorded by no manure in ‘Imperial’. Control treatment showed the lowest values for all the parameters studied. Combination of vermicompost and ‘Premium Crop’ cultivar was found the best among all other treatment combinations, including in respect of net return (Tk. 234099/ha) and BCR (3.08).Res. Agric. Livest. Fish. Vol. 11, No. 2, August 2024: 197-204